Identification of novel genes and pathways in colorectal cancer exosomes: a bioinformatics study - Huang, Qiuxiang; Shen, Ziyang; Zang, Rujin; Fan, Xiaoyan; Yang, Li; Xue, Mei (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Colorectal cancer (CRC) is a major public health problem, being the leading causes of mortality and morbidity worldwide. Exosomes are crucial to the molecular pathogenesis of CRC. It is essential to investigate the key differentially expressed genes (DEGs) in CRC exosomes. Methods: The DEGs between CRC patients and normal participants were screened using microarray data downloaded from the Gene Expression Omnibus (GEO) and exoRBase database. Gene ontology (GO), pathway enrichment analysis, protein-protein interaction (PPI) network, module analysis, overall survival (OS) analysis of hub genes and functional annotation of DEGs were performed. Results: A total of 149 DEGs in CRC exosomes and 1,507 DEGs in CRC tissues were identified with selecting criteria of P value